2016
DOI: 10.3389/fphys.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Na+, K+-ATPase on Glutamate Signaling in Neurodegenerative Diseases and Senescence

Abstract: Decreased Na+, K+-ATPase (NKA) activity causes energy deficiency, which is commonly observed in neurodegenerative diseases. The NKA is constituted of three subunits: α, β, and γ, with four distinct isoforms of the catalytic α subunit (α1−4). Genetic mutations in the ATP1A2 gene and ATP1A3 gene, encoding the α2 and α3 subunit isoforms, respectively can cause distinct neurological disorders, concurrent to impaired NKA activity. Within the central nervous system (CNS), the α2 isoform is expressed mostly in glial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 331 publications
(386 reference statements)
0
43
0
6
Order By: Relevance
“…FXYD2 and ATP4A ) in the prioritized gene list also warrants further investigation, but both have been implicated in processes important for HD pathogenesis, namely glutamate- and Wnt-signaling respectively. 31, 43, 44 Like GPR161, ATP4A has also been shown to have important functions in the cilia, 44 which may be relevant for HD since HTT is required for ciliogenesis. 19 Finally, since sonic hedgehog signaling was implicated through both the top TWAS genes and module based analyses, further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%
“…FXYD2 and ATP4A ) in the prioritized gene list also warrants further investigation, but both have been implicated in processes important for HD pathogenesis, namely glutamate- and Wnt-signaling respectively. 31, 43, 44 Like GPR161, ATP4A has also been shown to have important functions in the cilia, 44 which may be relevant for HD since HTT is required for ciliogenesis. 19 Finally, since sonic hedgehog signaling was implicated through both the top TWAS genes and module based analyses, further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have receptors for serotonin, norepinephrine, GABA, acetylcholine, AMPA, and NMDA glutamate receptor, as well for group I, II, and III metabotropic glutamate receptors, variations in the concentrations of these mediators could interfere with microglial function and morphology, as well as in the recognition of neuronal activity by the microglia [21,22]. Glutamate, an important excitatory neurotransmitter of the CNS, acts mostly in the hippocampus, cortex, and caudate nucleus through its metabotropic and ionotropic receptors, NMDA, AMPA, and Kainate and plays an important role in the processes of learning and memory formation, as well as in motor behavior and brain development [23]. The hyperglutamatergic hypothesis of autism is based on studies that showed high levels of glutamate in the serum, lower levels of the enzymes glutamate acid decarboxylase 65 and 67 (GAD65 and GAD67) [24,25], and the presence of increased gliosis in these patients [11].…”
Section: Microglia and Neurotransmission Alterationsmentioning
confidence: 99%
“…Through interactions with Src tyrosine kinases and IP3-receptors, Na,K-ATPases mediate the activation of Src tyrosine kinase-and intracellular Ca +2 -dependent signaling cascades, respectively (Aperia et al, 2016;Madan et al, 2016). Although classically described as a compound that affects the heart, ouabain is emerging as a potent neuroprotective agent (Kinoshita et al, 2016), and the Na + /K + -ATPase α 3 isoform plays an important role in the control of spatial learning and memory (Holm et al, 2016). Taken together, these observations make a role for brain α-Klotho as a regulator of Na,K-ATPasedependent cell signaling an exciting suggestion.…”
Section: What Does Brain α-Klotho Do?mentioning
confidence: 99%